Pelatihan Pembuatan Portofolio Digital Menggunakan Aplikasi Google site sebagai implementasi dari Kurikulum Merdeka di Desa Langkan, Kecamatan Langgam Kabupaten Pelalawan - Isjoni, M. Yogi Riyantama; Hermita, Neni; Putra, Riki Apriyandi; Aryani, Nini (Journal of Community Engagement Research for Sustainability, 2023)
The development of the times will create updates including the application of the independent learning curriculum, especially in terms of the use and utilization of e-learning. This era of digitalization is a challenge for teachers, all forms of activities through the electronic system are no longer manual. The current portfolio is website-based, regarding the collection of works, Learning Designs, Learning Implementation Plans, Student Worksheets are no longer in manual form but can be displayed using digital devices. This Digital Portfolio is in the form of media, using the google sites application which aims as a reflection and evaluation tool. The purpose of this service is to provide training and hands-on practice related to portfolio creation, and participants are required to bring a laptop. The implementation of the activity was carried out on July 14, 2022 at the Langkan village office, langgam district, Pelalawan regency. As a result of these devotion activities, the Master can create and understand how to use it